KEeLaN: assesment of turkish local authorities’ front offices on the internet through the context of e-europe basic services to determine the e-goverment stages and back office integration of the best-practices based on the efqm key elements - Arslan, Aykut (My University, 2006)
Bu araştırma üç aşamadan oluşmaktadır. İlk aşamada Türkiye’deki yerel yönetimlerin mevcut durumları incelenmiş ve e-devlet ile ilgili temel göstergeler ortaya konmuştur. 3228 adet yerel yönetim birimi belediyelerden oluşmakta ve bu birimler araştırmamızın örneklemini meydana getirmektedir. İkinci aşamadaysa web sitesi olan 969 yerel yönetimden 104 tanesi, e-hizmet verdiklerinden dolayı bir çevrimiçi taramadan geçirilmişlerdir. Amacımız eAvrupa çerçevesinde belirlenmiş 9 temel hizmette en gelişmiş düzeyi tutturanlardan 20 tanesini en iyi örnek olarak seçmektir. Üçüncü aşamada, EFQM mükemmellik modelinden geliştirilmiş bir kıyaslama anketi anahtar kişilere gönderilmiştir. Kıyaslama sonucunda amaç, yerel yönetimlerin arka bürolarındaki değişimin boyutunu ve derecesini ortaya çıkarmaktır. Sonuçlar SPSS aracılığıyla analiz edilmiştir. Sonuçlar sırasıyla EFQM’de yer alan 5 temel grupta sunulmuştur. Bunlar liderlik, politika ve strateji, çalışanlar, işbirlikleri ve kaynaklar ve süreçlerden oluşmaktadır. Ancak daha sonra eklenen altıncı madde, yöresel işbirliği, özellikle konunun yerel yönetimler olmasından dolayı, KEeLAN konsorsiyumu tarafından kıyaslama aracında kullanılmıştır. Tüm sonuçlar Avrupa yerel yönetimlerininkilerle karşılaştırılmıştır. Bu karşılaştırmalarla, her iki aşama için değişik bir bakış açısı vermek hedeflenmiştir; öncelikle Türk yerel yönetimlerinin e-hizmet düzeyleri değerlendirilmiş ve ardından arka bürolarının değişim dereceleri ile performansları ortaya konmuştur. Sonuçlar anlamlı olduğu kadar ilginçtir de. Her ne kadar web sitesine sahip Türk yerel yönetimleri sayıca az olsa da e-hizmet sağlamada mükemmel örnekler sergilemişlerdir.

This research is comprised of three phases. In the first phase it explores the recent situation of the Turkish local authorities on e-Government by pointing out the basic indicators. 3228 Turkish local governments were the municipalities and form the base sampling framework of this study. For the second phase, from 969 units, 104 of these authorities offering e-service provisions were selected so as to perform a web-scan. The objective was to find 20 best practice cases under the context of 9 basic services agreed by e-Europe framework. In the third phase, a benchmarking tool developed from European Foundation for Quality Management (EFQM) elements was sent to these authorities’ key personnel. The aim of this benchmarking assessment was to explore the degree of change and performance in the back office organizations of the 20 best practice local authorities. SPSS was used to analyze the data. The summary results were presented in the order of 5 key elements of EFQM, starting with leadership, policy and strategy, people, partnership and resources, and processes. The sixth element, regional context, was added later by the Key Elements of Electronic Local Authorities’ Networks (KEeLAN) consortium due to the specific focus on this aspect. The overall results were compared with the European local authorities’ results. The intention of the comparisons was to give a general outlook from the both phases; to value the maturity levels of the Turkish local governments on e-services and the degree of change and performance of their back-offices. The results were however significant as well as interesting. Albeit the low number of web ownership among the Turkish local governments, they displayed excellent examples of e-services.
Keywords: E-Devlet; Genel yönetim; Üretim yönetimi; Yönetim ve Organizasyon_İnternet